A Broad Spectrum Racemase in Pseudomonas putida KT2440 Plays a Key Role in Amino Acid Catabolism - Radkov, Atanas D.; Moe, Luke A. (Frontiers in Microbiology, 2018)
The broad-spectrum amino acid racemase (Alr) of Pseudomonas putida KT2440 preferentially interconverts the L- and D-stereoisomers of lysine and arginine. Despite conservation of broad-spectrum racemases among bacteria, little is known regarding their physiological role. Here we explore potential functional roles for Alr in P. putida KT2440. We demonstrate through cellular fractionation that Alr enzymatic activity is found in the periplasm, consistent with its putative periplasm targeting sequence. Specific activity of Alr is highest during exponential growth, and this activity corresponds with an increased accumulation of D-lys in the growth medium. An alr gene knockout strain (Dalr) was generated and used to assess potential roles for the alr gene in peptidoglycan structure, producing soluble signaling compounds, and amino acid metabolism. The stationary phase peptidoglycan structure did not differ between wild type and Dalr strains, indicating that products resulting from Alr activity are not incorporated into peptidoglycan under these conditions. RNA-seq was used to assess differences in the transcriptome between the wild type and Dalr strains. Genes undergoing differential expression were limited to those involved in amino acid metabolism. The Dalr strain exhibited a limited capacity for catabolism of L-lysine and L-arginine as the sole source of carbon and nitrogen. This is consistent with a predicted role for Alr in catabolism of L-lysine by virtue of its ability to convert L-lysine to D-lysine, which is further catabolized through the L-pipecolate pathway. The metabolic profiles here also implicate Alr in catabolism of L-arginine, although the pathway by which D-arginine is further catabolized is not clear at this time. Overall, data presented here describe the primary role of Alr as important for basic amino acid metabolism.